Evaluation of Touchdown Loop-Mediated Isothermal Amplification for the Detection of Giardia duodenalis - Márton Hartdégen; András József Laki; Kolos Farkasvölgyi; Kristóf Iván; Judit Plutzer (Parasitologia)
Giardia duodenalis is a flagellated protozoan pathogen causing parasitic enteric disease outbreaks worldwide. Among detection methods, loop-mediated isothermal amplification (LAMP) has high selectivity and sensitivity, and the detection time is lower than that of conventional molecular methods. In this study, three published Giardia LAMP primer sets were tested and adapted to touchdown LAMP conditions. The measurement time, the volume of reagents, the effect of the denaturation step, different kinds of polymerases, and the presence or absence of betaine on the reaction were tested and evaluated. Based on the results of this study, the 66–60 °C range touchdown LAMP with the use of betaine, 90 °C denaturation step, Bst 2.0 WarmStart® DNA Polymerase, and the primer set of Momoda et al. were the optimal conditions. We increased the analytical sensitivity of the LAMP reaction to 7.8- and 8-fold higher than the previously published methods for G. duodenalis assemblages A and B, with detection limits of 20 and 19.5 fg/assay, respectively, instead of 156 fg/assay. The detection time was less than 49 min for G. duodenalis assemblage A and less than 35 min for assemblage B, compared to the previously published 60 min. Our optimized LAMP protocol can be directly applied to improve Giardia LAMP tests in routine testing laboratories, could be implemented in standard diagnostic or environmental monitoring workflows, and can be used for the development of Giardia LAMP point-of-care devices or high-throughput systems.